(3BOGH GdSGdcjf hcdGe Ggd GdJMbjb hGdUhajI GdhGUdjfs - (3eLghds; (3SYjO feOHhT , WGgQ Hf bGSe Hf CMeO GdCfUGQj, SYjO feOHhT,J (B771 (3g` s
(3ChdgG (B:s
(3ceG de jcf ajg JQLjM de jfSH Edi NGWQ dGSJdRGeg GdJQLjM s
(3BNQgG (B:s
(3hGgOfG GdUQGW GdeSJbje hGdfgL Gdbhje Efc QDha QMje GfJgi fbdkG Yf LhGgQ Gdabg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B222s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdJUha hGdBOGH GdTQYjIs